The acceptance of international mobile wallet among generation Y in Klang valley - Chong, Michelle Jin Yee; Wong, Chao Rong (2019)
The purpose of this research is to study the factors affecting the Acceptance of International Mobile Wallet among Generation Y in Klang valley. This study determines the factors affecting the Acceptance of International Mobile Wallet among Generation Y in Klang valley by using quantitative approach where questionnaire was distributed to 203 respondents aged between 1939. This study focuses on how perceived ease of use, perceived usefulness, perceived risk and perceived security affects the Acceptance of International Mobile Wallet among Generation Y in Klang valley. In our findings, perceived ease of use and perceived usefulness significantly affects the Acceptance of International Mobile Wallet whereas, perceived risk and perceived security do not have significant relationship with the Acceptance of International Mobile Wallet. Moreover, we found out that perceived usefulness has the greatest influence on the Acceptance of International Mobile Wallet among Generation Y in Klang valley. This study will be useful for mobile wallet providers, policy makers, merchants, future researchers and readers as Malaysia is still in infant stage when it comes to mobile wallet industry.